2012
DOI: 10.5539/ijef.v4n6p11
|View full text |Cite
|
Sign up to set email alerts
|

The Risk-return Trade-off in Emerging Stock Markets: Evidence from Saudi Arabia and Egypt

Abstract: This paper examines empirically the trade-off between risk (conditional volatility) and expected returns for the Saudi Arabian and Egyptian stock indices over the period of January 1, 2007 to December 30, 2011. The empirical analysis of the paper is carried out by means of the generalized autoregressive conditional heteroscedastic (GARCH) in mean methodology including both symmetric (GARCH-M) and asymmetric (EGARCH-M) models. The results show that the dynamic risk-return relationship is quite different between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…A positive (and statistically significant) coefficient λ implies that returns carry a risk premium, and vice versa. In the context of stock markets, until recently a number of studies have applied different versions of GARCH-M models [e.g., Abdalla (2012) and Guo and Neely (2008)].…”
Section: Methodsmentioning
confidence: 99%
“…A positive (and statistically significant) coefficient λ implies that returns carry a risk premium, and vice versa. In the context of stock markets, until recently a number of studies have applied different versions of GARCH-M models [e.g., Abdalla (2012) and Guo and Neely (2008)].…”
Section: Methodsmentioning
confidence: 99%
“…They concluded the absence of causality in Pakistan and Korea but suggested the availability of such causality in India and the Philippines. Furthermore, Abdalla (2012) and Rahman & Uddin (2009) demonstrated that there is no causal relationship between foreign exchange market performance and stock returns in emerging capital markets. Phylaktis & Ravazzolo (2003) studied long-term and short-term dynamics of the relationship among the stock market and the exchange rates in Pacific Basin countries during 1980-1988 period and concluded that the two variables are positively co-related.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…The results demonstrated that the volatility of KSA stock market returns have decreased over years, and that correlations between markets have increased. Abdalla, (2012) studied the risk-return trade-off in emerging stock markets (Evidence from KSA & Egypt). The results show that the dynamic risk-return relationship is quite different between the Saudi and the Egyptian markets.…”
Section: Introductionmentioning
confidence: 99%